Solvent engineering for high conversion yields of layered raw materials into large-scale freestanding hybrid perovskite nanowires. Issue 37 (13th September 2018) - Gu, Jianmin; Wu, Jingxiao; Jin, Cuihong; Sun, Xiao; Yin, Baipeng; Zhang, Guang Cong; Wen, Bin; Gao, Faming
Abstract : We demonstrate a facile solvent-engineering technology to prepare large-scale freestanding perovskite nanowires by the conversion of the intermediate phase strategy. Abstract : Hybrid organic–inorganic perovskite nanowires have received considerable attention for applications in optoelectronic fields; however, practical implementation of perovskite nanowires into optoelectronic devices is often hindered by low product yields, scaled-up synthesis, or overall lack of synthetic control. Herein, we report novel insights into large-scale freestanding lead halide perovskite nanowires using a series of solvent effects. A facile pathway for converting layered raw materials to nanowires with high conversion yields can facilitate the large-scale applications of nanowires, which could help us understand the unique aspects of the formation chemistry of the materials. We introduced a two-step process to obtain perovskite nanowires without an impurity phase that first involves the formation of Pb-containing nanowires with the poor solvent drip method. Subsequently, the as-prepared Pb-containing precursors can be used as morphology templates for converting completely into perovskite nanowires with high conversion yields of 83% through a series of solvent effects, such as solvent-driven, solvent-removing, solvent-exchange and solvent-growth. The synthetic strategy was demonstrated to be applicable for other perovskite-based materials, which can offer a comprehensive understanding of the formation mechanism of perovskite-based materials.